Health service utilization, unmet healthcare needs, and the potential of telemedicine services among Korean expatriates - Ho Young Kim; Ju Young Kim; Hwa Yeon Park; Ji Hye Jun; Hye Yeon Koo; In Young Cho; Jinah Han; Yuliya Pak; Hyun Jung Baek; Ju Yeon Lee; Sung Hee Chang; Jung Hun Lee; et al. (BMC, 2018)
Abstract Background With the significant growth of migration and expatriation, facilitated by increased global mobility, the number of Koreans living abroad as of 2016 is approximately 7.4 million (15% of the Korean population). Healthcare utilization or health problems, especially among expatriates in developing countries, have not been well researched despite the various health risks these individuals are exposed to. Consequently, we identified the health utilization patterns and healthcare needs among Korean expatriates in Vietnam, Cambodia, and Uzbekistan. Methods This cross-sectional survey examined 429 Korean expatriates living in Vietnam (n = 208), Cambodia (n = 60), and Uzbekistan (n = 161) who had access to the Internet and were living abroad for at least 6 months. A 67-item questionnaire was used, and feedback was received via an online survey program. Stepwise logistic regression analyses were performed to evaluate factors associated with unmet healthcare needs and preferences of certain type of telemedicine. Results We found that 45.5% (195/429) of respondents had used medical services in their country of stay. Among those who visited health institutions > 3 times, the most popular choice was general hospitals (39.4%, 15/38); however, they initially visited Korean doctors' or local doctors' offices. The most essential criteria for healthcare service facilities was a "skilled professional" (39.3%, 169/429), 42% wanted a health program for chronic disease management, and 30% wanted specialized internal medicine. A substantial number wanted to access telemedicine services and were willing to pay for this service. They were particularly interested in experts' second opinion (61.5%, 264/429) and quick, 24-h medical consultations (60.8%, 261/429). Having unmet healthcare needs and being younger was strongly associated with all types of telemedicine networks. Conclusions Nearly half of the expatriates in developing countries had unmet healthcare needs. Telemedicine is one potential solution to meet these needs, especially in developing countries.